Left ventricle fibrosis associated with nonsustained ventricular tachycardia in an elite athlete: Is exercise responsible? A case report - Poussel, M.; Djaballah, K.; Laroppe, J.; Brembilla-Perrot, B.; Marie, P.-Y.; Chenuel, B. (Journal of Athletic Training, 2012)
Abstract: Objective: To emphasize the potentially harmful effects of high-intensity exercise on cardiac health and the fine line between physiologic and pathologic adaptation to chronic exercise in the elite athlete. This case also highlights the crucial need for regular evaluation of symptoms that suggest cardiac abnormality in athletes. Background: Sudden cardiac death (SCD) of young athletes is always a tragedy because they epitomize health. However, chronic, high-intensity exercise sometimes has harmful effects on cardiac health, and pathologic changes, such as myocardial fibrosis, have been observed in endurance athletes. In this case, a highly trained 30-year-old cyclist reported brief palpitations followed by presyncope feeling while exercising. Immediate investigations revealed nonsustained ventricular tachycardia originating from the left ventricle on a stress test associated with myocardial fibrosis of the left ventricle as shown with magnetic resonance imaging. Despite complete cessation of exercise, life-threatening arrhythmia and fibrosis persisted, leading to complete restriction from competition. Differential Diagnosis: Hypertrophic cardiomyopathy, arrhythmogenic right ventricular cardiomyopathy, myocarditis, postmyocarditis, use of drugs and toxic agents, doping, and systemic disease. Treatment: The arrhythmia could not be treated with catheter ablation procedure or drug suppression. Therefore, the athlete was instructed to withdraw completely from sport participation and to have a medical follow-up twice each year. Uniqueness: To our knowledge, no other report of left ventricle exercise-induced fibrosis associated with life-threatening arrhythmia in a living young elite athlete exists. Only postmortem evidence supports such myocardial pathologic adaptation to exercise. Conclusions: To prevent SCD in young athletes, careful attention must be paid to exercise-related symptoms that suggest a cardiac abnormality because they more often are linked to life-threatening cardiovascular disease.